Chromophore Induced Effects in Iron(III) Complexes - Schmitz, Lennart; Argüello Cordero, Miguel A.; Al-Marri, Mohammed J.; Schoch, Roland; Egold, Hans; Neuba, Adam; Steube, Jakob; Bracht, Bastian Johannes; Bokareva, Olga S.; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
In the search for noble metal free photocatalytic systems, iron is the dream candidate. To increase excited state lifetimes of iron complexes, the multichromophoric approach is promising, combining organic chromophores with photoactive iron complexes, potentially enabling a reservoir effect. We present a series of chromophore-functionalized complexes based on the parental FeIII complex [Fe(ImP)2][PF6] (HImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)). The four organic chromophores benzene, naphthalene, anthracene, and pyrene are attached to the ImP-ligand in para-position to the coordination site to systematically investigate the influence of the steric demand and electronic properties of the chromophore on charge transfer lifetimes as well as photodynamics. A thorough ground state characterization was conducted in addition to investigations of the excited state dynamics by transient absorption spectroscopy and streak camera emission measurements. The conclusions drawn are supported by extensive DFT calculations. The emission coefficients could be significantly improved by the addition of chromophores. After excitation of the complexes with larger chromophores, coplanarization of the backbone and complex motif occurs to stabilize the formal charge. This results in population of a superligand state that exhibits a much faster radiationless relaxation to the ground state compared to the parent complex, hindering a reservoir effect.
Keywords: Photo

Isostructural Series of a Cyclometalated Iron Complex in Three Oxidation States - Steube, Jakob; Fritsch, Lorena; Kruse, Ayla; Bokareva, Olga S.; Demeshko, Serhiy; Elgabarty, Hossam; Schoch, Roland; Alaraby, Mohammad; Egold, Hans; Bracht, Bastian Johannes; Schmitz, Lennart; Hohloch, Stephan; et al. (Inorganic Chemistry)
An isostructural series of FeII, FeIII, and Fe(IV)complexes [Fe(ImP)2]0/+/2+ utilizing the ImP 1,1′-(1,3-phenylene)-bis(3-methyl-1-imidazol-2-ylidene) ligand, combining N-heterocy-clic carbenes and cyclometalating functions, is presented. The strong donor motif stabilizes the high-valent Fe(IV) oxidation state yet keeps the FeII oxidation state accessible from the parent Fe(III)compound. Chemical oxidation of [Fe(ImP)2]+ yields stable [FeIV(ImP)2]2+. In contrast, [FeII(ImP)2]0, obtained by reduction,is highly sensitive toward oxygen. Exhaustive ground state characterization by single-crystal X-ray diffraction, 1H NMR,Mössbauer spectroscopy, temperature-dependent magnetic measurements, a combination of X-ray absorption near edge structureand valence-to-core, as well as core-to-core X-ray emission spectroscopy, complemented by detailed density functional theory (DFT) analysis, reveals that the three complexes[Fe(ImP)2]0/+/2+ can be unequivocally attributed to low-spin d6, d5, and d4 complexes. The excited state landscape of the Fe(II) and Fe(IV) complexes is characterized by short-lived 3MLCT and 3LMCT states, with lifetimes of 5.1 and 1.4 ps, respectively. In the FeII-compound, an energetically low-lying MC state leads to fast deactivation of the MLCT state. The distorted square-pyramidal state, where one carbene is dissociated, can not only relax into the ground state, but also into a singlet dissociated state. Its formation was investigated with time-dependent optical spectroscopy, while insights into its structure were gained by NMR spectroscopy.
Keywords: Photo